Qualidade da dieta de crianças de escolas municipais de Belo Horizonte, Minas Gerais: avaliação e proposta de otimização - Paula Martins Horta (2016)
Introduction: Food consumption evaluation in childhood can contribute to dietary inadequacies identification and guide health interventions. Thus, studying multiple interrelated dietary components adjusted for within person variance is highly recommended. In sequence, diet optimization can be used to predict changes that allow improve dietary quality while deviating the least from dietary habits presented. Objective: to evaluate usual diet quality among children from municipal schools of Belo Horizonte, Minas Gerais, and to propose its otimization. Methods: Cross-sectional study. Data collection were realized between March 2013 and August 2015 and included: sex, age, address (to posterior vulnerability risk evaluation), school meals consumption, anthropometry (weight and height), food consumption (one 24-hour dietary recall - 24HR for the whole sample and two 24HR for a subsample). Diet quality was evaluated by Healthy Eating Index 2010 (HEI-2010). The National Cancer Institute multiple dietary components model was applied to estimate usual diet quality. In addition, diet quality optimization by linear programming was applied and childrens mean energy requirement (1,740 kcal) was the objective function and the main food items consumed the sample (90% of all foods) were the decision variables. Constraints related to HEI-2010 components aimed to provide at least 80% of their maximum score and nutrients content was defined to achieve current recommended standards. Results: The sample comprised 1,357 children and the HEI-2010 total score was 55.08. Children with poorer diet quality (<10th) scored less than 44.72 and children with higher diet quality (>90th) scored more than 65.22. Components of higher adequacy were: total protein foods and beans and greens; and the ones with lower adequacy: refined grains, fatty acids, dairy and sodium. Small differences in HEI-2010 score (about 2-3 points) were noted among categories of sex, social vulnerability risk and school meals consumption. Regarding results from diet optimization, the model was feasible after substituting skimmed milk for whole milk. Intake of some foods had to be increased (in comparison to the mean observed intake): whole grains (52.06 times), oil (11.06 times), milk (3.15 times), fruits (3 times), tomato, cabbage and green collard (3 times). In contrast, rice, non-industrialized bread and pasta was reduced to 40% of the mean and ultra-processed foods were decreased to no lower than 10% of the mean. Conclusion: The study pointed inadequacies in children's diet quality and suggested changes in order to improve it. Increasing natural and minimally processed foods consumption in needed, especially whole grains, oil, milk, fruits and vegetables, in contrast to ultraprocessed products and refined grains intake that have to be reduced. These results can be used in school meal menu definition and in food and nutrition education activities.